The cardiovascular complications of SARS-CoV-2 infection - Naidu, Srihari (Henry Stewart Talks, 2020)
Entry of SARS-CoV-2 into the cardiovascular system, The direct and indirect effects of SARS-CoV-2 on the heart, How to identify and diagnose heart damage during infection, Possible long-term cardiovascular complications, How heart diseases are being affected by the COVID-19 pandemic